ZADANIA ZORIENTOWANE NA EKSPRESJĘ TEATRALNĄ JAKO NARZĘDZIE WSPIERAJĄCE ROZWÓJ KREATYWNOŚCI JĘZYKOWEJ STUDENTA FILOLOGII ROMAŃSKIEJ - Blachowska-Szmigiel, Marzena (Neofilolog, 2019)
The goal of this paper is to outline the possibilities of the use of drama techniques as a tool to support development of the linguistic creativity of students of French. The paper consists of three parts. In parts 1 and 2 the author presents the theoretical foundations of the teaching techniques proposed, and these are then presented in part 3.